2016
DOI: 10.1038/srep18974
|View full text |Cite
|
Sign up to set email alerts
|

Is costly punishment altruistic? Exploring rejection of unfair offers in the Ultimatum Game in real-world altruists

Abstract: In the Ultimatum Game (UG), incurring a cost to punish inequity is commonly termed altruistic punishment. This behaviour is thought to benefit others if the defector becomes more equitable in future interactions. However, clear connections between punishment in the UG and altruistic behaviours outside the laboratory are lacking. We tested the altruistic punishment hypothesis in a sample of extraordinarily altruistic adults, predicting that if punishing inequity is predictive of altruism more broadly, extraordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 51 publications
3
48
0
Order By: Relevance
“…At the same time, neither subscale was significantly associated with need for cognition, a trait measure of motivation to engage in effortful cognition. These results are consonant with recent studies that found that extreme altruists who donated their kidneys to strangers exhibit higher empathic concern ( Brethel-Haurwitz et al, 2016 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…At the same time, neither subscale was significantly associated with need for cognition, a trait measure of motivation to engage in effortful cognition. These results are consonant with recent studies that found that extreme altruists who donated their kidneys to strangers exhibit higher empathic concern ( Brethel-Haurwitz et al, 2016 ).…”
Section: Discussionsupporting
confidence: 91%
“…The 2D model also allows us to better clarify the relationship between utilitarian moral thinking and empathic concern. Again, the negative relationship between utilitarian decision-making and empathic concern suggested by multiple prior studies ( Choe & Min, 2011 ; Conway & Gawronski, 2013 ; Gleichgerrcht & Young, 2013 ; Patil & Silani, 2014 ) is highly puzzling given the historical and, on some views, strong theoretical tie between classical utilitarianism and empathy ( Hare, 1981 ; Smart, 1961/ 1973 ) and evidence tying empathic concern to extreme altruism to distant strangers ( Brethel-Haurwitz et al, 2016 ). But our results show that this association is driven exclusively by the instrumental harm dimension of utilitarianism and that empathic concern is at the same time positively associated with impartial beneficence, utilitarianism’s positive core.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence we have covered here broadly supports the view that, compared to the economic dimension of ideology, the social dimension is more consistently related to punitiveness, at least in the ultimatum game. The reason social conservatism and related variables are often associated with punitive behaviour in the ultimatum game may be that punitiveness in this game seems to reflect normative rather than pro-social or anti-social behaviour (Brañas-Garza et al, 2014;Brethel-Haurwitz et al, 2016;Yamagishi et al, 2012). 3…”
Section: Norm Enforcementmentioning
confidence: 99%
“…For example, individuals who have anonymously donated their kidneys evince greater amygdala responsiveness than do matched controls (Marsh, Stoycos, Brethel-Haurwitz, Robinson, VanMeter, & Cardinale, 2014). Anonymous kidney donors are also high in dispositional sympathy (Brethel-Haurwitz, Stoycos, Cardinale, Huebner, & Marsh, 2016). Recall that sympathy is elicited by the perception of others' distress, and generates altruistic motivation (Batson, 2011).…”
mentioning
confidence: 99%